Understanding the potentials and challenges of agricultural technology based crowdfunding in Malaysia / Mohammad Fauzy Tambi, Azlina Hanif and Herwina Rosnan - Tambi, Mohammad Fauzy; Hanif, Azlina; Rosnan, Herwina (Universiti Teknologi MARA, 2022)
Crowdfunding is a new era financing alternative. It has been well accepted worldwide and the sustainability was empirically proven. Despite the popularity, rapid growth, and overwhelming acceptability worldwide, yet still to be unfamiliar relatively to many people. Especially in the Malaysian context where there is very little understand about how, why, where, when and what type of crowdfunding (business area) users prefer to engage. Accordingly, agriculture is yet to be among the Malaysian main industries since post-independence. However, as reported for the past couple of years, the Growth Domestic Product (GDP) for agriculture is still far behind Manufacturing and Services industries. Among the issues were low up take of agriculture technology and innovations due to high initial investment, high risk, hard to access for loan. As crowdfunding is a new emerging financing alternative, thus this paper is to understand the potentials and challenges of Agricultural Technology-Based Crowdfunding (ATCF). For a better understanding, we performed a qualitative study based on semi-structured interviews of above 18 years old Malaysian citizen. The respondents were randomly engaged. Data from the interviews were later transcribed into verbatim, analysed within and cross cases, coded, categorised, and grouped into the emerging themes. The findings were displayed in a table in responding to the research objectives. Few future research have also been identified and proposed to strengthen the study on the subject matter